DOES CORSS LISTING IN THE UK INCREASE A FIRM'S VALUE? - Ma, Ling (2006)
Cross-listing has gained increasing popularity these days, and many researchers have proposed different theories to explain its reasons and impacts, especially cross-listing in the US market. Doidge, Karolyi, and Stulz (2001) study 710 non-US firms that cross listed in the US market with a comparison group of 4078 firms and argue that cross listing premium exists, growth opportunities are valued more for cross-listed firms so as to give enough incentive for controlling shareholders to partially give up their private benefits, and that growth opportunities are valued more for cross-listed firms coming from countries with poorer protection of shareholder rights, as controlling shareholders could expropriate more private benefits in these countries.